The Evolution of AUSM Schemes - Liou, Meng-Sing (Defence Science Journal, 2010)
This paper focuses on the evolution of advection upstream splitting method (AUSM) schemes. The main ingredients that have led to the development of modern computational fluid dynamics (CFD) methods have been reviewed, thus the ideas behind AUSM. First and foremost is the concept of upwinding. Second, the use of Riemann problem in constructing the numerical flux in the finite-volume setting. Third, the necessity of including all physical processes, as characterised by the linear (convection) and nonlinear (acoustic) fields. Fourth, the realisation of separating the flux into convection and pressure fluxes. The rest of this review briefly outlines the technical evolution of AUSM and more details can be found in the cited references. Defence Science Journal, 2010, 60(6), pp.606-613, DOI:http://dx.doi.org/10.14429/dsj.60.580